Deep waters : mysteries on the waves - Edwards, Martin, 1955- (Poisoned Pen Press, 2019)
"From picturesque canals to the swirling currents of the ocean, a world of secrets lies buried beneath the surface of the water. Dubious vessels crawl along riverbeds, while the murky depths conceal more than one gruesome murder. The stories in this collection will dredge up delight in crime fiction fans, as watery graves claim unintended dwellers and disembodied whispers penetrate the sleeping quarters of a ship's captain. How might a thief plot their escape from a floating crime scene? And what is to follow when murder victims, lost to the ocean floor, inevitably resurface?"--